Cytomegalovirus infection in autologous bone marrow transplantation: a retrospective analysis from a tertiary care centre in Pakistan - Farrukh Ali Khan; Fawad Qureshi; Urooj Haider Hashmi (Journal of the Pakistan Medical Association, 2025)
Objective: To determine the frequency, management and outcome of cytomegalovirus infections in autologous bone marrow transplant recipients. Method: The retrospective study was conducted at the Dow University Hospital, Karachi, in February 2025, and comprised medical record of patients who underwent autologous bone marrow transplant between February 1, 2019, and December 31, 2024. The data noted included age, gender, primary diagnosis, chemotherapy protocol, neutrophil and platelet engraftment, cytomegalovirus serology pre-transplant, and outcomes on day +30 and day +100. Data was analysed using SPSS 16. Results: Of the 36 patients, 21(58.3%) were males and 15(41.7%) were females. The overall mean age was 35.29±11.79 years. The primary diagnosis in 21(58.3%) patients was Hodgkin lymphoma, 11(30.6%) had multiple myeloma, and 4(11.1%) had non-Hodgkin lymphoma. All the 36(100%) patients were seropositive for cytomegalovirus-immunoglobulin G pre-transplant. The median duration for neutrophil engraftment was 11 days (interquartile range: 14.75-10 days) and for platelet engraftment it was 12.5 days (interquartile range: 21-11 days). Of the total, 6(16.7%) patients had cytomegalovirus reactivation with a median time of 35 days (interquartile range: 42-19 days). Overall 30-day survival rate was 34(94.4%) and 100-day survival rate was 32(88.9%). The corresponding values in cytomegalovirus reactivation cases were 6(100%) and 5(83.3%), respectively. Conclusion: There was a significant reactivation of cytomegalovirus in patients having undergone autologous bone marrow transplant, but since they were regularly monitored and treated pre-emptively, there was no major negative impact on the outcomes. Key Words: CMV reactivation, Autologous bone marrow transplant.